2006
DOI: 10.1016/j.nuclphysb.2006.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the topological susceptibility in two colour QCD across the finite density transition

Abstract: The behaviour of the topological susceptibility χ in QCD with two colours and 8 flavours of quarks is studied at nonzero temperature on the lattice across the finite density transition. It is shown that the signal of χ drops abruptly at a critical chemical potential µ c , much as it happens at the finite temperature and zero density transition. The Polyakov loop and the chiral condensate undergo their transitions at the same critical value µ c . At a value µ s of the chemical potential, called saturation point… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 79 publications
8
64
4
Order By: Relevance
“…2, we plot the topological susceptibility, and we see that it decreases but does not vanish when regularization II is used; the effect of regularization I, approximately at the same temperature, a result that has already been found in [15,22]; the new finding is that the critical temperature with the new regularization is now T c ≃ 177…”
Section: Numerical Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…2, we plot the topological susceptibility, and we see that it decreases but does not vanish when regularization II is used; the effect of regularization I, approximately at the same temperature, a result that has already been found in [15,22]; the new finding is that the critical temperature with the new regularization is now T c ≃ 177…”
Section: Numerical Resultssupporting
confidence: 58%
“…Several lattice calculations (see [21] and references therein) indicate a sharp decrease of the topological susceptibility with temperature at zero density, and, more recently [22], it was shown that, at a fixed T and by varying the chemical potential µ, a critical µ is found, where the quark condensate and the topological susceptibility drop and the Polyakov loop raises; its derivatives vary sharply.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario was subsequently confirmed by simulations with staggered lattice fermions [5,9]. More recent simulations have found evidence for a second transition at larger µ to a deconfined phase, as evidenced by a non-vanishing Polyakov loop [11] and by a fall in the topological susceptibility [12]. In this regime thermodynamic quantities scale according to the expectations of free field theory (also referred to as "Stefan-Boltzmann" (SB) scaling), namely n q ∝ µ 3 , and energy density ε ∝ µ 4 [11].…”
Section: Introductionmentioning
confidence: 61%
“…We have chosen β = 9.0 sufficiently close to the continuum limit for the DR formalism to be trustworthy, and start with a point with T = 2T c according to (12); from Table 1 this corresponds to κ = 0.3620027, λ = 0.0020531. For this parameter set, we have explored system volumes 8 3 × L t , with L t = 16, 32, 64 and 128.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation